2021
DOI: 10.1038/s41598-021-92933-2
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled volatilome analysis as a useful tool to discriminate asthma with other coexisting atopic diseases in women of childbearing age

Abstract: The prevalence of asthma is considerably high among women of childbearing age. Most asthmatic women also often have other atopic disorders. Therefore, the differentiation between patients with atopic diseases without asthma and asthmatics with coexisting diseases is essential to avoid underdiagnosis of asthma and to design strategies to reduce symptom severity and improve quality of life of patients. Hence, we aimed for the first time to conduct an analysis of volatile organic compounds in exhaled breath of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 87 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…The infants included in the present study from the NELA cohort will be followed up during childhood (follow-up visits at 18 months, 5 years, and 7 years of age). 16,18 In this regard, a prospective assessment will be performed to check the association of the outcomes of lung function parameters and exhaled VOCs with the future development of respiratory/atopic diseases such as asthma. Thus, it would be possible to determine if lung function tests together with | 1287 monitoring of oxidative stress by exhaled breath analysis in healthy infants during the first months of life could be a useful strategy for early respiratory disease detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The infants included in the present study from the NELA cohort will be followed up during childhood (follow-up visits at 18 months, 5 years, and 7 years of age). 16,18 In this regard, a prospective assessment will be performed to check the association of the outcomes of lung function parameters and exhaled VOCs with the future development of respiratory/atopic diseases such as asthma. Thus, it would be possible to determine if lung function tests together with | 1287 monitoring of oxidative stress by exhaled breath analysis in healthy infants during the first months of life could be a useful strategy for early respiratory disease detection.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy infants (infants born at term) included in this study belong to the prospective birth cohort nutrition in early life and asthma (NELA) ( www.nela.imib.es ). 16 , 17 , 18 Recruitment of the infants was conducted over 36 months (from March 2015 to April 2018) and was carried out at the control visit of the 20th week of pregnancy at the Maternal‐Fetal Unit of the Hospital Universitario Virgen de la Arrixaca (Murcia, Spain). Inclusion criteria were as follows: maternal age between 18 and 45 years; habitual residence in Health Area I, and some districts of Health Areas VI and VII of the Region of Murcia; planning to live in the same place of residence for at least 2 years; intention to deliver in the reference hospital; Spanish Caucasian origin; singleton pregnancy; unassisted conception; and normal ultrasound at 20 weeks of pregnancy (no major malformations).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 2-Ethyl-1-hexanol is an endocrine disruptor associated with the development of several respiratory diseases, such as asthma [46,[49][50][51][52][53]. Indeed, high levels of 2-ethyl-1-hexanol in exhaled breath have recently been linked to asthma with coexisting atopic diseases in women [27]. By contrast, in the present study, a significant relationship was not observed between dampness exposure and human-exhaled-breath levels of aromatic compounds, which are traditionally reported to be linked with SBS development [32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the VOCs involved in oxidative stress can be detected in exhaled breath [23]. In this regard, it has been reported that the metabolite profiles detected in exhaled breath or exhaled breath condensate (EBC) can discriminate between asthmatics and healthy controls, and between controlled asthmatics and asthmatics with exacerbations [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%